Analisis Pengaruh Dimensi PIECES terhadap Kepuasa Pelanggan pada Layanan Fotografi Otomotif di Jakarta - Dandy Agus Pratanto; Qori Halimatul Hidayah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the factors influencing customer satisfaction in automotive photography services in Jakarta using the PIECES method, which consists of six main components: Performance, Information, Economy, Control, Efficiency, and Service. The research approach used was quantitative with multiple linear regression analysis. Data were collected through questionnaires distributed to 100 respondents who had used automotive photography services in Jakarta. The research instrument was designed to measure customer perceptions of each PIECES component and their overall level of satisfaction. The analysis results show that all PIECES components have a positive effect on customer satisfaction. Service and Performance factors emerged as the most dominant variables in increasing satisfaction. This indicates that responsive, friendly, and professional service quality, as well as fast and reliable system performance, play an important role in shaping positive customer perceptions. The Information component also contributes by providing accurate and relevant information, while Economy reflects customers' assessment of price affordability. The Control aspect helps maintain consistent results, and Efficiency supports the smoothness of the service process. These findings have practical implications for creative service industry players, particularly in the automotive photography sector. Improving service quality (Service) can be done through human resource training, customer interaction management, and rapid response to consumer needs. Meanwhile, optimizing system performance (Performance) can be achieved by using high-quality photography equipment, effective workflows, and the use of digital technology. Overall, this study confirms that the PIECES-based approach can be a strategic reference in increasing customer satisfaction, while strengthening the competitiveness of automotive photography businesses in an increasingly competitive market.